2010
DOI: 10.3758/pbr.17.4.556
|View full text |Cite
|
Sign up to set email alerts
|

Personality predicts temporal attention costs in the attentional blink paradigm

Abstract: Accuracy for a second target is reduced when it is presented within 500 msec of a first target. This phenomenon is called the attentional blink (AB). A diffused attentional state (via positive affect or an additional task) has been shown to reduce the AB, whereas a focused attentional state (via negative affect) has been shown to increase the AB, purportedly by influencing the amount of attentional investment and flexibility. In the present study, individual differences in personality traits related to positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 35 publications
2
23
0
1
Order By: Relevance
“…The result of Experiment 2 was consistent with previous studies, showing that conscious fearful faces increase the AB [37]. This deteriorated AB may be due to a more focused attentional state caused by unmasked fearful faces [34], [36]. Interestingly, a reverse pattern was found in Experiment 1: fearful faces with restricted awareness reduced the AB magnitude.…”
Section: Discussionsupporting
confidence: 90%
“…The result of Experiment 2 was consistent with previous studies, showing that conscious fearful faces increase the AB [37]. This deteriorated AB may be due to a more focused attentional state caused by unmasked fearful faces [34], [36]. Interestingly, a reverse pattern was found in Experiment 1: fearful faces with restricted awareness reduced the AB magnitude.…”
Section: Discussionsupporting
confidence: 90%
“…As hypothesized, individuals with high externalizing displayed a significantly greater AB than individuals with low externalizing. Although other studies have investigated individual differences in AB performance (MacLean & Arnell, 2010; Martens & Valchev, 2009; Carr, Nigg & Henderson, 2006; Wolf, Carpenter, Warren, Zeier, Baskin-Sommers & Newman, in press), we believe ours is the first study to document an association between AB performance and the latent externalizing construct.…”
Section: Discussionmentioning
confidence: 65%
“…More relevant to the current study is evidence from unselected samples that individual differences in personality traits predict AB magnitude. Greater negative affect and neuroticism are associated with a larger AB (i.e., reduced attentional control), whereas greater positive affect, extraversion, and openness are associated with a smaller AB (MacLean & Arnell, 2010; MacLean et al, 2010). Similarly, Rokke et al (2002) found that moderately-to-severely dysphoric college students exhibited impaired AB performance relative to nondysphoric and mildly dysphoric students, and the authors noted that these results could have been as likely due to group differences in state anxiety as to differences in depression.…”
Section: Discussionmentioning
confidence: 99%